SDM-PEB: Spatial-Depthwise Mamba for Enhanced Post-Exposure Bake Simulation - Yu, Ziyang; Xu, Peng; Wang, Zixiao; Zhu, Binwu; Wang, Qipan; Lin, Yibo; Wang, Runsheng; Yu, Bei; Wong, Martin (2025 62nd ACM/IEEE Design Automation Conference (DAC), 2025)
The post-exposure bake (PEB) process is a critical step in semiconductor lithography, directly impacting resist profile accuracy and circuit pattern fidelity. Precise modeling of PEB is essential for controlling photoacid diffusion and inhibitor reactions. In this paper, we introduce SDM-PEB, an advanced modeling framework designed to enhance the accuracy of PEB simulations by capturing both intra-layer spatial dependencies and inter-layer depthwise interactions. Leveraging a unique hierarchical feature extractor with overlapped patch merging and efficient self-attention, our approach effectively captures both coarse and fine features at multiple scales. The spatial-depthwise Mamba-based attention unit, centered on a customized selective scan and structured state space model, efficiently captures spatial and depthwise dependencies, enabling precise 3D PEB simulation. Additionally, a PEB focal loss and differential depth divergence regularization term improve the sensitivity to both spatial and depthwise variations, addressing inherent data imbalances in 3D PEB simulations. Our framework is validated with commercial rigorous model, and experimental results demonstrate that the SDM-PEB outperforms previous methods in accuracy and efficiency.